FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN PENYAKIT JANTUNG KORONER (PJK) ( - Lucky Bachtiiar; Rian Arie Gustaman; Sri Maywati (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2023)
CHD is a disease caused by a blockage or narrowing of the coronary arteries, due to an atherosclerotic process that supplies blood flow to the heart, as well as the accumulation of fat in the coronary arteries, thereby blocking blood flow to the heart. The purpose of this study was to analyze the risk factors associated with the incidence of coronary heart disease at the Subang District General Hospital. The research method is quantitative with an observational approach and a case control design in the subject of heart disease inpatients with a total sample of 93 consisting of 33 case samples and 66 control samples. The statistical test used is chi-square with a level of α = 0.05. The results showed that there was a significant relationship between hypertension (p-value 0.042), diabetes mellitus (p-value 0.039), cholesterol (p-value 0.020) and the incidence of coronary heart disease. There was no significant relationship between BMI (p-value 0.041), age (p-value 0.487) and gender (p-value 0.504) with the incidence of coronary heart disease. Suggestions for providing health promotion to patients and the public through putting up posters, distributing brochures, leaflets and health communication approaches by officers both personally and in mass. Carry out more routine control and check-ups related to hypertension, diabetes mellitus and cholesterol according to the recommendations of health workers, consume drugs regularly.